A cytochrome P450 class I electron transfer system from Novosphingobium aromaticivorans. - Bell, S; Dale, A; Rees, N; Wong, L (2010)
Cytochrome P450 (CYP) enzymes of the CYP101 and CYP111 families from Novosphingobium aromaticivorans are heme monooxygenases that catalyze the hydroxylation of a range of terpenoid compounds. CYP101D1 and CYP101D2 oxidized camphor to 5-exo-hydroxycamphor. CYP101B1 and CYP101C1 oxidized beta-ionone to predominantly 3-R-hydroxy-beta-ionone and 4-hydroxy-beta-ionone, respectively. CYP111A2 oxidized linalool to 8-hydroxylinalool. Physiologically, these CYP enzymes could receive electrons from Arx, a [2Fe-2S] ferredoxin equivalent to putidaredoxin from the CYP101A1 system from Pseudomonas putida. A putative ferredoxin reductase (ArR) in the N. aromaticivorans genome, with high amino acid sequence homology to putidaredoxin reductase, has been over-produced in Escherichia coli and found to support substrate oxidation by these CYP enzymes via Arx with both high activity and coupling of product formation to NADH consumption. The ArR/Arx electron-transport chain has been co-expressed with the CYP enzymes in an E. coli host to provide in vivo whole-cell substrate oxidation systems that could produce up to 6.0 g L(-1) of 5-exo-hydroxycamphor at rates of up to 64 microM (gram of cell dry weight)(-1) min(-1). These efficient biocatalytic systems have potential uses in preparative scale whole-cell biotransformations.